Hypoplastic AI with Highly Variable Expressivity Caused by ENAM Mutations. (August 2018) - Koruyucu, M.; Kang, J.; Kim, Y.J.; Seymen, F.; Kasimoglu, Y.; Lee, Z.H.; Shin, T.J.; Hyun, H.K.; Kim, Y.J.; Lee, S.H.; Hu, J.C.C.; Simmer, J.P.; et al.
Tooth enamel, the hardest tissue in the human body, is formed after a complex series of interactions between dental epithelial tissue and the underlying ectomesenchyme. Nonsyndromic amelogenesis imperfecta (AI) is a rare genetic disorder affecting tooth enamel without other nonoral symptoms. In this study, we identified 2 novel ENAM mutations in 2 families with hypoplastic AI by whole exome sequencing. Family 1 had a heterozygous splicing donor site mutation in intron 4, NM_031889; c.123+2T>G. Affected individuals had hypoplastic enamel with or without the characteristic horizontal hypoplastic grooves in some teeth. Family 2 had a nonsense mutation in the last exon, c.1842C>G, p.(Tyr614*), that was predicted to truncate the protein by 500 amino acids. Participating individuals had at least 1 mutant allele, while the proband had a homozygous mutation. Most interestingly, the clinical phenotype of the individuals harboring the heterozygous mutation varied from a lack of penetrance to a mild hypoplastic enamel defect. We believe that these findings will broaden our understanding of the clinical phenotype of AI caused by ENAM mutations.